2020
DOI: 10.3390/jcm9113563
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of T Cell Immunoglobulin and Mucin-Domain Containing Molecule 3 in Patients with Systemic Lupus Erythematosus

Abstract: Objective: T cell immunoglobulin and mucin-domain-containing molecule 3 (TIM-3) is implicated in the development of various autoimmune diseases. We aimed to investigate the levels of soluble TIM-3 (sTIM-3) and their associations between clinical parameters in patients with systemic lupus erythematosus (SLE). Methods: Serum samples were collected from 65 patients with SLE and 35 age-matched healthy controls (HCs). The SLE Disease Activity Index 2000 (SLEDAI-2K) and the Systemic Lupus International Collaborating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
4
5
0
Order By: Relevance
“…This discrepancy from our study could be explained by the variations in the sample size of SLE patients studied. Also, our results are in agreement with Asano et al [10] who found that serum level of Tim-3 was negatively correlated with C3 and C4 levels. They showed that a further longitudinal study with a large number of SLE patients with different disease phenotypes is required to determine the role of serum Tim-3 in SLE pathophysiology.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This discrepancy from our study could be explained by the variations in the sample size of SLE patients studied. Also, our results are in agreement with Asano et al [10] who found that serum level of Tim-3 was negatively correlated with C3 and C4 levels. They showed that a further longitudinal study with a large number of SLE patients with different disease phenotypes is required to determine the role of serum Tim-3 in SLE pathophysiology.…”
Section: Discussionsupporting
confidence: 93%
“…Tim-3 has been found to play an important role in SLE [ 21 .] In our study, we found a highly significant increase in serum levels of Tim-3 in patient group when compared with controls, this was in agreement with Asano et al [10], who found that serum levels of Tim-3 were significantly higher in SLE patients than controls. They demonstrated that a possible link between Tim-3 and SLE and, circulating Tim-3 works in SLE patients as an anti-immune mediator.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the setting of autoimmunity, aberrant TIM3 expression is closely correlated with the development of systemic lupus erythematosus (SLE) (90)(91)(92)(93)(94)(95), multiple sclerosis (96,97), and rheumatoid arthritis (98). However, the role of TIM3 underlying different autoimmune diseases has yet to be explored.…”
Section: Tim3 Signaling Participates In Acute and Chronic Kidney Inflammationmentioning
confidence: 99%